A importância do projeto político pedagógico dentro do âmbito escolar (PPP): análise do PPP da escola municipal de Ensino Fundamental II Anete Farias da Silva no município de Oiapoque-AP - QUARESMA, Eliete Barbosa (Instituto Federal do Amapá, 2021)
The political-pedagogical project (PPP) is a document that defines the guidelines, goals and methods for the educational institution to achieve the goals it proposes. The PPP aims to improve the teaching capacity of the school as an entity inserted in a democratic society and political interactions. This document is responsible for guiding the way the school plans its strategic actions and establishes goals for the development of the teaching and learning process, which encourages the development of pedagogical actions and strategies. The research methodology was based on the documental analysis of the PPP of the Municipal Elementary School II Anete Farias da Silva, located in the municipality of Oiapoque-AP and is configured as a qualitative investigation. The main objective of this article is to analyze the importance of the PPP for the entire school body, as a guide for actions to be developed at school.